Menentukan Pengaruh Makroekonomi dan Internal Bank Terhadap Risiko Kredit pada Bank Umum Konvensional Indonesia - Keisha Nabiila Endriani; Maria Safitri; Diana Puspitasari; Vicky Oktavia (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2026)
This study was conducted to identify the impact of macroeconomic variables and internal banking factors on the level of credit risk, known as Non-Performing Loans (NPL), in conventional commercial banks in Indonesia. The macroeconomic variables considered included the rupiah exchange rate, interest rates, and GDP (Gross Domestic Product), while the internal bank factors included ROE (Return On Equity), LDR (Loan to Deposit Ratio), and CAR (Capital Adequacy Ratio). A quantitative approach was applied using secondary data from 2019 to 2024 and a panel regression technique with the REM model. The study sample included 10 conventional commercial banks selected using a purposive sampling method. The study findings revealed that interest rates and ROE had a significant negative effect on NPLs, while LDR showed a significant positive impact on NPLs. On the other hand, the rupiah exchange rate, GDP, and CAR did not show a significant effect on NPLs. Overall, all independent variables jointly influence credit risk.